Mobilisasi Generasi Z di Kota Kendari pada Pilkada 2024: Kajian Literatur Sistematis Strategi Komunikasi Politik - Sitti Rahmah Sari Mainuru; Jeanny Maria Fatimah; Indrayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has changed the pattern of political communication in Indonesia, especially among Generation Z who dominate new voters in the 2024 Kendari Regional Election. This research aims to analyze the effectiveness of digital political communication and the role of social media in building Generation Z political engagement at the local level. Using a qualitative descriptive approach through case studies, data was obtained from in-depth interviews with young voters and campaign teams, as well as analysis of candidates' social media content. The results show that TikTok and Instagram are the most effective media in building emotional and ideological closeness between candidates and young voters through visual content, authentic storytelling, and two-way interaction. The phenomenon of algorithmic visibility shows that social media algorithms affect the exposure of political messages, so that content personalization strategies are a decisive factor in increasing Gen Z's digital participation. These findings underscore the importance of participatory, value-based, and adaptive political communication strategies to social media algorithms in realizing an inclusive digital democracy.